Penerapan Teknologi Tepat Guna Aquaponik Dan Budikdamber Menggunakan Alat Autofeeder Di Al Qolam Fish And Farm Kota Blitar - Ayu Cahyasusanti; Gideon Setyo Budi Witjaksono; Noor Rizkiyah (Universitas Maritim AMNI Semarang, 2023)
The increasing number of urban residents with the increasingly narrow operational land of the fish farming system, telnology is made in a bucket by utilizing automatic feed in the form of an auto feeder made from used cans with the aim of reducing can waste then the inside of the can add with a dynamo and given a food player useful for dropping food with a period of 15 minutes using an automatic feeder and developing kale plant cultivation. This activity is a form of community service carried out by students of the National Development University